The spatial relationship between auto transportation and the change in urban land uses in Mansourieh - Mohammed, Mohammed Atea (Al-Adab Journal, 2022)
The research aims to highlight the spatial relationship between car transport roads and the changes taking place in urban land uses in Mansourieh. The study showed that there are three main patterns for the streets of Mansuriyya, represented by the (organic, radial, and retina-quadruple), and the length of the streets in the city of Mansuriyya combined reached (40,400) m, and its area reached (573800) m2. The study confirmed the existence of a correlation between the motorway roads and the change of urban land uses for the city of Mansuriyya, as the study showed a variation in the urban land values ​​and areas according to the type of street, and that commercial use overshadows the streets of the study area, especially on the main streets, and the study showed a positive relationship Between the transportation methods and the variables related to the functional and urban structure of Mansourieh.